2020
DOI: 10.1007/s12026-020-09159-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in therapeutic applications of neutralizing antibodies for virus infections: an overview

Abstract: Antibodies are considered as an excellent foundation to neutralize pathogens and as highly specific therapeutic agents. Antibodies are generated in response to a vaccine but little use as immunotherapy to combat virus infections. A new generation of broadly cross-reactive and highly potent antibodies has led to a unique chance for them to be used as a medical intervention. Neutralizing antibodies (monoclonal and polyclonal antibodies) are desirable for pharmaceutical products because of their ability to target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 142 publications
(50 reference statements)
0
38
0
Order By: Relevance
“…Currently, there are no licensed CHIKV vaccines available for use; however, potential vaccine candidates are classified into seven types: inactivated vaccines, subunit vaccines, live-attenuated vaccines, recombinant virus-vectored vaccines, virus-like particle vaccines, chimeric vaccines, and nucleic acid vaccines ( 9 , 10 ). Virus-like particles (VLPs) are generated by expression of the CHIKV structural cassette from a DNA expression plasmid transfected into human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no licensed CHIKV vaccines available for use; however, potential vaccine candidates are classified into seven types: inactivated vaccines, subunit vaccines, live-attenuated vaccines, recombinant virus-vectored vaccines, virus-like particle vaccines, chimeric vaccines, and nucleic acid vaccines ( 9 , 10 ). Virus-like particles (VLPs) are generated by expression of the CHIKV structural cassette from a DNA expression plasmid transfected into human cells.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been demonstrated that the presence [77] and triggering [78] of CR1/2 on B cells is required to mount sustained antigen-specific antibody production. In the case of a pathogen-specific nano-vaccine, the candidate antigen would be a pathogen-specific surface protein in order to induce neutralizing antibodies [79]. Alternatively (or in addition), a pathogen-derived protein, which would be apparent on the surface of infected cells [80], would be a suitable antigen, inducing the production of antibodies that recognize infected cells, and trigger classical complement activation [81] or antibody-dependent cytotoxicity [82].…”
Section: Discussionmentioning
confidence: 99%
“…Both polyclonal and monoclonal neutralizing antibodies can be potentially used as antivirals because of their capacity to target specific epitopes. Despite some limitations of neutralizing antiviral antibodies as therapeutic agents, they have potential for prevention and treatment of several viral infections (Ebola, HIV, chikungunya virus, MERS-CoV, SARS-CoV, and SARS-CoV-2) (38). The CRISPR/Cas-9 technology is being used in different antiviral strategies, including: (i) modification of viral entry receptors, (ii) knock-down of host viral factors, (iii) induction of host restrictions factors, (iv) excision and removal of viral genomes that are integrated in the host genome or persisting as episomes (39,40).…”
Section: Strategies and Trends In Antiviral Researchmentioning
confidence: 99%